REPRESENTATION OF A COMPANY WHEN CONTRACTING WITH ANOTHER PERSON UNDER SOUTH AFRICAN COMPANY LAW Makate v Vodacom (Pty) Ltd [2016] ZACC 13 - Vela Madlela; Palollo Michael Lehloenya (Obiter, 2018)
A company is an artificial person and has no mind, will or hands of its own. It is, therefore, compelled to act through human agents. The board of directors is responsible for the management and direction of the business affairs of the company. Under South African company law the directors’ powers of management are statutorily entrenched (S 66(1) of the Companies Act 71 of 2008). The board of directors may, however, delegate its powers to an individual director (or individual directors), a committee of the board, a managing director or other officers of the company. Before an individual director or officer of the company can conclude a binding transaction on behalf of their company, they must have the authority to do so. In South Africa, the issue of authority to enter into a transaction or agreement on behalf of a company is dealt with using the principles of the law of agency.The crisp issue in this note relates to the circumstances in which an individual company director or officer who, when contracting with another person, purports to be acting on behalf of the company will bind the company. In the recent case of Makate v Vodacom (Pty) Ltd ([2016] ZACC 13 (hereinafter “Makate v Vodacom”)), which involved a claim for reasonable compensation by the inventor of the concept of “Please Call Me” against Vodacom (Pty) Limited (hereinafter “Vodacom”), the Constitutional Court dealt specifically with the authority of a director to conclude a contract with a third party on behalf of the company. This note discusses Makate v Vodacom and the approach of the court regarding when a company will be bound by contracts concluded by its director or another person purporting to represent the company in a transaction with a third party. It examines the main judgment of Jafta J and the concurring judgment of Wallis J in relation to the legal nature of ostensible authority in the absence of actual authority.The note further looks at the issue of prescription, which Vodacom in its defence raised against the claim for compensation brought by Mr Makate. It explores the circumstances in which prescription can be successfully invoked to deflect a contractual claim brought against a company, the impact of the Constitution in this area of the law and whether the claim lodged by Mr Makate amounted to a “debt” for purposes of the Prescription Act (68 of 1969). To this end, again, both the main judgment of Jafta J and the concurring judgment of Wallis J are examined. This is followed by critical insights on the implications of this case and some concluding remarks.